The Paradox of the Presidency: The Difference a President makes in Institutional Functioning at Three Community Colleges - Levin, John S. (Canadian Journal of Higher Education, 1992)
Do presidents make a difference? Presidential impact on colleges and universities has been called into question for decades. Most recently, there is evidence to suggest that institutional functioning may not be affected by who presidents are or by what presidents do (Birnbaum, 1989). Such questioning fits within the mainstream of thinking on the presidency at higher education institutions. This thinking conveys a dualism of perceptions about presidents (Benezet et al., 1981). On the one hand, presidents are seen to have both power and authority to direct their institutions; on the other hand, presidents are seen as having limited control over their institutions. Twenty-four governing board members at three Canadian community colleges were interviewed to determine whether and to what extent presidents are seen to make a difference in institutional functioning. This study concludes that from the perspective of board members, presidents do make a difference in institutional functioning. Presidential impact can be seen in public and government perceptions of the college, in institutional decision-making, and in the preservation of college philosophy. Furthermore, the president is the educational leader, not as a determiner of educational programs or teaching performance, but rather as the communicator of institutional orientations and actions.